Meddelelser om Kreaturudførslen til Storbritanien. Foredrag, d. 11te Decbr. 1867. - Mestring, G. (Tidsskrift for Landøkonomi, 2018)
Meddelelser om Kreaturudførslen til Storbritanien. Foredrag, d. 11te Decbr. 1867.